(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Digitization and advanced conservation in India are exceptionally imperative to save social legacy accumulations, and furthermore make them available to the researchers and public. The examiner has endeavored to ponder the digitization and computerized protection exercises in the select libraries in India. There are archive assets, particularly compositions and uncommon books, which are truly profitable; however they are not permitted to be gotten to because of worries of harm to unique reports. By digitization, the firsts can be securely verified and the duplicates utilized by researchers for any required data.